KNEE: COMPARISON OF ANGLE Q BETWEEN SOCCER PLAYERS OF FIELD AND COLLEGES STUDENT. (Fiep Bulletin - online, 2015)
The objective of the research is to compare which of the samples, Soccer players of Field or Colleges student have greater Angle Q in the knee?  Femural angle Q is defined by Kuhn, et al (2002), Nester, et al, (2001), Livingston, et al (1999), "and the angle formed in the intersections of Anterior Superior Illiac Spine (A.S.I.S.), the medial point of Patela (PM) and the Tubercle of the Tibia (TT) ", forming two perpendicular lines in quadríceps. According to Livingston, et al, (1999), "the angle in Q above and the 15 20 degrees this directly associated with patelo-femurais syndromes constantly attack in football players for extrinsic and intrinsic factors of the modality". The research and of quantitative characteristic with sampling of 30 individuals, being, 15 Soccer players of Field and 15 Colleges student.  The used methodology was the gauging with camera assuming a methodological error of 1 the 5 mm second metanálise of Nester, et al, (2001).  The presented results demonstrate one strong significance in (ME) for (JFC) e (U), with high force (F=12,7) and significance assumed for (P
Keywords: Angle Q; Soccer; Pathologies